(untitled) (Research, Society and Development, 2020)
The work aims to evaluate the extent to which parasitic species are capable of compromising the growth, flowering and productivity of host plants. This is a bibliographic review study carried out on articles, dissertations and monographs published in the years 1987 to 2020, the search occurred in the Capes Journals, Google Scholar, SciELO and in books of the area of ​​interest, the descriptors used were Parasitic plants, Host plants and parasitic interactions, after reading the titles and abstracts, 62 works read in Portuguese and English were selected for the preparation of this manuscript. Through the bibliographic review, it became possible to understand and analyze the relationship between parasitic species and host species, parasitism occurs both in the aerial and underground parts, in the aerial part it is classified in halo and hemiparasites, while in Organs underground organs it has as parasitic agents, nematodes, capable of causing damage in the growth and development of these species, due to the intense withdrawal of nutrients and water, resulting in the onset of diseases classified as infectious / biotic or non-infectious / abiotic. The attacks from parasitic species, induce that the host species generate their own defense system, by the formation of physical and biological barriers, when surviving they are able to possess the Acquired Systemic Resistance (RSA) and the production of compounds by the secondary metabolism. Therefore, parasitic species are capable of generating direct damage in the growth, flowering and productivity of host species, which is only reversed when the plant generates subsequent defense, in order to guarantee the existence of the species in the environment.